STRATEGI KOMUNIKASI VISUAL DALAM PERANCANGAN KOMIK SEJARAH DAN RANGKAIAN UPACARA METATAH UNTUK REMAJA HINDU MELALUI MEDIA WEBTOON - I Nyoman Miyarta Yasa; Ni Luh Kadek Mei Ananda Sari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Metatah is a Hindu tradition of filing six teeth from left to right which is part of Manusia Yadnya. This tradition aims to control sad ripu, which are six enemies within humans. From the initial data collection questionnaire, data was obtained that there is still a lack of understanding among Hindu teenagers regarding the history, stages, and meaning of the metatah ceremony which is a challenge that has the potential to reduce the quality of yadnya. Webtoon media was chosen as a means of education because of its practicality, accessibility via the internet, and flexibility to be read at any time. This study uses a descriptive qualitative research method to describe in detail the process of designing an educational webtoon with a design thinking design method that includes five main steps, namely empathize, define, ideate, prototype, and test. Data collection techniques are carried out using observation, interview, and documentation methods. The data obtained are analyzed qualitatively through a categorization process which is then used in designing stories and visuals. This project produces a webtoon comic entitled